Systemic CD4+ T cell phenotype and activation status in intermediate uveitis. Issue 3 (20th February 2004) - Murphy, C C; Duncan, L; Forrester, J V; Dick, A D
Abstract : Aim: To investigate peripheral blood lymphocyte phenotype in patients with intermediate uveitis using CD69, chemokine receptor, and cytokine expression. Methods: Peripheral blood lymphocytes of 18 patients with idiopathic intermediate uveitis and 6 patients with presumed sarcoid intermediate uveitis were evaluated for CD4 + T cell expression of CD69, CCR4, CCR5, CXCR3 and the intracellular cytokines IFNγ, TNFα, and interleukin (IL)-10 by flow cytometry, and for IL-2, IL-4, IL-5, IL-10, IFNγ, and TNFα production following unstimulated and activated culture using cytokine bead array and compared with healthy control subjects. Results: The expression of CD69 and TNFα by peripheral blood CD4 + lymphocytes of patients with idiopathic intermediate uveitis and presumed sarcoid intermediate uveitis was significantly higher than control subjects (p = 0.002 and p<0.05, respectively). The ratios of the concentrations of IL-2:IL-5 and IFNγ:IL-5 in supernatants of activated peripheral blood lymphocyte cultures were significantly higher in patients with presumed sarcoid intermediate uveitis than control subjects. Conclusions: This study implicates TNFα in the pathogenesis of intermediate uveitis, highlighting the potential role of anti-TNF treatments for this disease. Studies of Th1:Th2 cytokine ratios suggested polarisation of the immune response towards Th1 in presumed sarcoid intermediate uveitis despite clinically quiescent systemic disease.